Exploring the anti-obesity effects of Lactobacillus in C57BL/6 mice : mechanisms, interventions, and future directions - Sharoen Lim, Yu Ming; E-Jayn, Chong; Weng Yan, Mah; Yan, Pan; Chee Mun, Fang; Chandrika, Murugaiah; Mustafa, Alshagga (Oxford University Press, 2025)
Lactobacillus species show strong potential in fighting obesity-related inflammation and metabolic issues. Obesity causes inflammation in adipose tissue, which harms insulin sensitivity and leads to fat buildup. Lactobacillus strains like Lactobacillus gasseri, Lactobacillus reuteri, and Lactobacillus plantarum help regulate lipid metabolism by boosting key genes, preventing fat cell formation, and encouraging fat breakdown. They also produce short-chain fatty acids (SCFAs) that improve gut health, activate metabolic pathways, and reduce inflammation. Studies in animals have shown that Lactobacillus can reduce body weight, fat, and inflammation, with Lactobacillus plantarum being especially effective in improving gut microbiota and liver function. When combined with other probiotics or prebiotics, these strains work even better, enhancing lipid metabolism and reducing inflammation. These results suggest that Lactobacillus could be an effective way to manage obesity and related health problems by influencing metabolism, gut health, and inflammation. However, more research, particularly human clinical trials, is needed to confirm its potential as a dietary treatment for obesity.